Comparative study of ZnO and TiO2 nanoparticles: physicochemical characterisation and toxicological effects on human colon carcinoma cells. Issue 8 (December 2012) - De Angelis, Isabella; Barone, Flavia; Zijno, Andrea; Bizzarri, Loreline; Russo, Maria Teresa; Pozzi, Roberta; Franchini, Fabio; Giudetti, Guido; Uboldi, Chiara; Ponti, Jessica; Rossi, Francois; De Berardis, Barbara
Abstract Despite human gastrointestinal exposure to nanoparticles (NPs), data on NPs toxicity in intestinal cells are quite scanty. In this study we evaluated the toxicity induced by zinc oxide (ZnO) and titanium dioxide (TiO2) NPs on Caco-2 cells. Only ZnO NPs produced significant cytotoxicity, evaluated by two different assays. The presence of foetal calf serum in culture medium significantly reduced ZnO NPs toxicity as well as ion leakage and NP-cell interaction. The two NPs increased the intracellular amount of reactive oxygen species (ROS) after 6 h treatment. However, only ZnO NPs increased ROS and induced IL-8 release both after 6 and 24 h. Experimental data indicate a main role of chemical composition and solubility in ZnO NPs toxicity. Moreover our results suggest a key role of oxidative stress in ZnO NPs cytotoxicity induction related both to ion leakage and to cell interaction with NPs in serum-free medium.